Uzinové syndrómy periférnych nervov horných koncatín - Matejcík, V (Rozhledy v chirurgii, 2002)
BACKGROUND: The author presents the results of surgery of entrapment syndromes of the peripheral nerves implemented at his department in the course of 10 years (1990-2000). MATERIAL AND METHODS: In 72 patients 90 operations were performed in the course of which 85 entrapment syndromes were treated. The carpal tunnel syndrome was recorded in 40 patients (55.6%), the cubital canal syndrome in 24 patients (33.3%). The other entrapment syndromes of the peripheral nerves of the upper extremities-8(11.1%) were classified as rare. In 13 patients the entrapment syndrome was bilateral, the carpal tunnel syndrome in 12 and the cubital canal syndrome in one patient. In 17 patients there were re-operations, incl. 12 re-operations after primary treatment in another department. The clinical picture of compressive syndrome was divided according to the intensity according to Dellon's classification into 3 grades. Grade I compression was found in 2 cases (2.8%) (2/2). Grade II compression was found in 8 patients (11.1%) (9/10). Grade III Patients with grade III compression-62 (86.1%) predominated (68/80). The values are expressed as the number of patients/number of entrapment syndromes. The effectiveness of the surgical operation was analyzed with regard to the degree of compression, length of compression and duration of symptoms. RESULTS: Excellent and satisfactory results were recorded in all cases with grade I and II compression and duration of symptoms up to 12 months. The position was worse in patients with grade III compression where excellent and satisfactory results were recorded in 62 cases (77.5%) and when the complaints persisted for more than 12 months, i.e. in 30 of 48 cases (62.5%). CONCLUSION: The decisive factor which influences the result of the operation is the grade of nerve compression and its duration. Decisive factors improving the results of surgery are age under 30 years and period of complaints shorter than one year, when the symptoms are not yet irreversible.
Keywords: Carpal Tunnel Syndrome; dospělí; Cubital Tunnel Syndrome; paže; lidé; Female; mužské pohlaví; syndrom karpálního tunelu; úžinové syndromy; Arm; syndrom kubitálního tunelu; Male; Nerve Compression Syndromes; Adult; ženské pohlaví; Humans